System response matrix calculation using symmetries for dual‐head PET scanners. Issue 3 (16th August 2013) - Liu, Yilong; Wang, Mengdie; Bai, Jing; Zhang, Hui
ABSTRACT Positron emission tomography (PET) scanner with dual‐head geometry offers better spatial resolution and higher sensitivity for dedicated application when compared with conventional full‐ring PET scanners. However, this configuration suffers from limited‐angle projection and depth‐of‐interaction (DOI) effects. Accurate modeling of the system response matrix (SRM) and its incorporation into iterative methods can help to obtain images with better quality. In this paper, we proposed a line‐of‐response (LOR) based symmetry approach to calculate the SRM of PET scanners with dual‐head geometry. Both Monte Carlo (MC) and analytically computed SRMs were obtained and named MC SRM and geometrical SRM respectively, with their performances been compared using simulated phantom studies. The point source study shows that the resolution in directions parallel to the detector is rather uniform, with a full width at half maximum (FWHM) of 0.6∼0.7 mm and 0.6∼0.8 mm using MC and geometrical SRMs respectively. While the spatial resolution in the direction perpendicular to the detector is much worse, when moving towards the detector panel from the field‐of‐view (FOV) center, the FWHM changes from 1.5 mm to 1.8 mm and 2.4 mm to 3.1 mm using MC and geometrical SRMs, which is caused by the missing of projection views. Images generated using MC SRM also show better stochastic quality and quantitative performance. © 2013 Wiley Periodicals, Inc. Int J Imaging Syst Technol, 23, 205–214, 2013